Saussurea tridactyla Sch. Bip.-derived polysaccharides and flavones reduce oxidative damage in ultraviolet B-irradiated HaCaT cells via a p38MAPK-independent mechanism - Guo Y; Sun J; Ye J; Ma W; Yan HL; Wang G (Dove Medical Press, 2016)
Yan Guo,1 Juan Sun,2 Juan Ye,1 Wenyu Ma,1 Hualing Yan,1 Gang Wang1 1Department of Dermatology and Venereology, Affiliated Hospital of Qinghai University, 2Department of Anatomy, Qinghai University Medical College, Xining, People’s Republic of China Objective: To investigate whether Saussurea tridactyla Sch. Bip.-derived polysaccharides and flavones exert apoptosis-inhibiting effects in ultraviolet B (UVB)-irradiated HaCaT cells.Methods: We divided HaCaT cells into low radiation UVB and high radiation UVB groups. Low radiation UVB and high radiation UVB groups were further divided into a control group, UVB radiation group (UVB group), S. tridactyla Sch. Bip.-derived polysaccharides and flavones low-dose group, and S. tridactyla Sch. Bip.-derived polysaccharides and flavones high-dose group. Cell viability and morphology were assayed by MTT and trypan blue staining. Superoxide dismutase activity, glutathione content, malondialdehyde content, and catalase activity test kits were used to detect superoxide dismutase activity, glutathione content, malondialdehyde content, and catalase activity, respectively. Cell apoptosis, intracellular Ca2+ levels, and mitochondrial membrane potential (ΔΨ) were detected by flow cytometry. Protein levels were analyzed by Western blotting and immunofluorescence.Results: S. tridactyla Sch. Bip.-derived polysaccharides and flavones were found to increase the absorbance of MTT, decrease cell death, alleviate the degree of cell edema, restore the cell morphology, reduce cell death fragments and chip phenomenon, increase superoxide dismutase activity, glutathione content, and catalase activity while decreasing the content of malondialdehyde, lowering the population of apoptotic cells, reducing the intracellular Ca2+ fluorescence, increasing the mitochondrial membrane potential (ΔΨ), increasing the expressions of p-38, p-53, Bcl-2, and decreasing the expressions of Bax and active-caspase-3.Conclusion: S. tridactyla Sch. Bip.-derived polysaccharides and flavones can reduce cell apoptosis to protect HaCaT cells from oxidative damage after UVB irradiation; however, this effect does not occur via the p38MAPK pathway. Keywords: Saussurea tridactyla Sch. Bip.-derived polysaccharides, flavones, oxidative damage, p38MAPK-independent mechanism